Penerapan Model Pembelajaran Berbasis Masalah Untuk Meningkatkan Kemampuan Berpikir Kritis Siswa Kelas IV di SD Negeri Johar Baru 15 - Hikmawati Hikmawati; Zulfan Zulfan; Yevi Sylvia Tantika (Unram Journal of Community Service, 2023)
The purpose of this community service activity is to improve the critical thinking skills of grade IV students at SD Negeri Johar Baru 15 through the application of a problem-based learning model. This activity was carried out 2 times, namely on 29 August 2022 and 12 September 2022. All 23 grade IV students participated in the activity. The implementation method includes five steps: 1) Orientation of students to the problem; 2) Organizing students to learn; 3) Guiding investigations; 4) Develop and present the work; 5) Analyse and evaluate the problem solving process. Critical thinking skills include four indicators: 1) Formulating problems; 2) Disclosing facts; 3) Give arguments; 4) Think inductively. Critical thinking ability data is obtained by administering a test at the end of each meeting. The results of the activity show that the indicator for formulating a problem at meeting 1 gets a score of 72, increasing at meeting 2 to 90; The indicator for disclosing facts at meeting 1 scored 68 and increased at meeting 2 to 86; For indicators giving arguments at meeting 1 getting a value of 70 increases at meeting 2 to 81; The inductive thinking indicator increased from 74 to 86. Thus it can be concluded that the application of the problem-based learning model has improved the critical thinking skills of fourth grade students at SD Negeri Johar Baru 15